Morphological Errors in Students’ Academic Writing: A Linguistic Study - Siti Ayu Nurhidayati (JELT : Journal of English Education, Teaching and Literature, 2026)
This study aims to analyze morphological errors in students’ academic writing from a linguistic perspective. It focuses on identifying the types of errors and examining the factors that contribute to their occurrence. This research employs a qualitative approach with a descriptive design. The data were collected from students’ academic writing assignments in an English as a Foreign Language (EFL) context using documentation techniques. The participants were selected purposively based on their involvement in academic writing activities. The findings reveal that students frequently make morphological errors in several categories, including affixation, pluralization, verb inflection, and word formation. Among these, errors in affixation and verb inflection are the most dominant. The study also finds that these errors are influenced by factors such as first language interference, limited vocabulary knowledge, and insufficient understanding of morphological rules. The study concludes that morphological errors significantly affect the quality and clarity of students’ academic writing. Therefore, it is important to enhance students’ morphological awareness through explicit instruction and continuous practice. This study is expected to contribute to the improvement of English language teaching, particularly in developing students’ writing skills and linguistic competence.